Lactobacilli spp. and Zataria multiflora essence as antibiotic substituent on broiler health and performance parameters. Issue 1 (31st December 2022) - Hedayati, Mahdi; Khalaji, Saeed; Manafi, Milad
Abstract: This experiment was conducted to evaluate the effects of commercial probiotics (Lactobacillus spp.) (LS) with Zataria multiflora essential oil (ZEO) and an antibiotic growth promoter (AGP) on broiler health and performance. In experiment 1, 300 one-day-old chicks (Ross 308) were assigned to one of 4 treatments, comprising five replicates per treatment in a completely randomised design. Dietary treatments included: basal diet (control), 0.25 and 0.50 g/kg LS, or 0.50 g/kg Flavomycine added to basal diet. In experiment 2, 225 one-day-old chicks, were assigned to one of 3 treatments, comprising five replicates per treatment in a completely randomised design Dietary treatments included: basal diet (control), 0.50 g/kg LS, or 1 g/kg ZEO added to the basal diet. The inclusion of LS increased body weight gain significantly ( P ≤ .05) at 42 days of age. Both AGP and LS reduced feed intake and feed conversion ratio compared to the control diet ( P ≤ .05). The lowest triglyceride, cholesterol, LDL and ALT were observed in chicks administered by LS compare to control and AGP ( P ≤ .05). The inclusion of LSdecreased triglyceride, cholesterol, LDL and ALT, and increased immune titre against IBD and IB compare to control and AGP ( P ≤ .05), and Intestinal health index were increased in LS group compared to control and AGP. The addition of ZEO, decreased LDL and ALT, and increased the immune titre against AI, ND and IBD compared to LS significantly ( P ≤ .001). The results showed that usage of LS (0.5 g/kg) population of salmonella and coliform bacteria were greatly reduced, while in ZEO fed birds, E. coli population of caeca was reduced considerably ( P ≤ .001). These results confirmed that LS and ZEO have effective on broiler chicken and can be considered a potent antibiotic replacer. HIGHLIGHTS: Use of antibiotic growth promoters (AGP) in poultry diets, has been banned worldwide. To control and eliminate of intestinal pathogens, and increase body weight and improve FCR, alternative procedures as adding phytogenic compounds and probiotics in the poultry diet. Lactobacilli spores and Zataria multiflora essence can decrease the microbial population of the caecum, and increase the intestinal health index.